Investigating the impact of information on the efficiency of smallholder dairy production systems in India and the lessons for livestock extension policy - Pratap S Birthal; Jaweriah Hazrana; Raka Saxena (Agricultural Economics Research Review, 2023)
Using data from a nationally representative farm survey and applying the instrumental variable method, this study has assessed the impact of information on the efficiency of smallholder dairy farming in India. There are four key highlights of this study. One, using information in farm decisions leads to an improvement in dairy productivity by about 15%. Two, different types of information have differential impacts — information on livestock management has a more significant effect than on health, breeding, and nutrition. Three, the payoff is larger for joint use of information than to any kind of information used in isolation. Four, there is also an information source effect — public extension system has a larger effect than any other information source.